The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6528/ab5cde
|View full text |Cite
|
Sign up to set email alerts
|

Ag nanoparticles decorated into metal-organic framework (Ag NPs/ZIF-8) for electrochemical sensing of chloride ion

Abstract: In this work, silver nanoparticles (Ag NPs) were decorated into the cavities of ZIF-8 to fabricate a novel Ag NPs/ZIF-8 modified glassy carbon electrode (GCE) for electrochemical sensing of chloride ion. Benefiting from the synergistic properties of ZIF-8 and Ag NPs, the Ag NPs/ZIF-8/GCE showed favorable performance towards chloride ion. For comparison, the electrochemical activity of Ag NPs wrapped by ZIF-8 (Ag NPs@ZIF-8) and Ag NPs coating on ZIF-8 (Ag NPs-on-ZIF-8) were also investigated and it was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Because of their relatively strong node-to-linker bonds, rigid framework structures, and regular pore size in the range of a few nanometers, Zr-MOFs have been reported as the porous supports to generate pore-confined metal NPs without further agglomeration. As mentioned previously that silver can be served as the active electrocatalyst for electrochemical nitrite detection, we reasoned that Ag NPs confined in the nanopores of a water-stable Zr-MOF should be an attractive candidate for nitrite sensors. A few recently published studies have reported the synthesis of composite materials composed of Zr-MOFs and Ag NPs. The use of Ag NPs incorporated in iron-, copper-, or zinc-based MOFs for electrochemical sensors has also been reported very recently. However, all the reported Ag NP–MOF composite materials have not been applied for electrochemical nitrite detection.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their relatively strong node-to-linker bonds, rigid framework structures, and regular pore size in the range of a few nanometers, Zr-MOFs have been reported as the porous supports to generate pore-confined metal NPs without further agglomeration. As mentioned previously that silver can be served as the active electrocatalyst for electrochemical nitrite detection, we reasoned that Ag NPs confined in the nanopores of a water-stable Zr-MOF should be an attractive candidate for nitrite sensors. A few recently published studies have reported the synthesis of composite materials composed of Zr-MOFs and Ag NPs. The use of Ag NPs incorporated in iron-, copper-, or zinc-based MOFs for electrochemical sensors has also been reported very recently. However, all the reported Ag NP–MOF composite materials have not been applied for electrochemical nitrite detection.…”
Section: Introductionmentioning
confidence: 99%
“…This innovative sticker technology and the emergence of new wearable gadgets and sensors give them hope. [3][4][5][6][7][8][9][10]…”
Section: Smart Stickers and Their Operationmentioning
confidence: 99%
“…[1][2][3][4][5] Although there are schemes for rapid diagnosis, however, smart, and non-invasive techniques are very few. [5][6][7][8][9][10][11][12][13] This short communication deals with a smart sticker which can detect CF at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…As an important anion, chloride ions (Cl À ) can be found almost everywhere in environmental water because it is used in many disinfectants, pesticides and production processes. [1][2][3] However, the accumulation of Cl À in manufacturing is prone to inducing polarization reactions which can lead to the acceleration of equipment corrosion. Also, if there is excessive Cl À in agricultural water, it will lead to soil salinization and acidification, thus affecting the growth of crops.…”
Section: Introductionmentioning
confidence: 99%